Implementasi Analisis Fast, Slow, Non Moving (FSN) Untuk Efesiensi Pengerjaan Picking Pada Gudang 3PL - Poncotoyo, Wahyu; Tatianan, Yana; Arhab, Abiyyu; Sholihah, Sita Aniisah; Saribanon, Euis (Jurnal Sistem Transportasi & Logistik, 2024)
The global fashion industry, including in Indonesia, is experiencing rapid growth with significant challenges in packaging and warehousing, as faced by PT. XYZ, a footwear distributor. This study applies Fast, Slow, Non-Moving (FSN) analysis to categorize items based on their movement speed, resulting in a 15% reduction in travel distance and a decrease in picking time for fast-moving items from 33.98 seconds to 26 seconds. The implementation of FSN also successfully reduced the packing cycle time from 2.61 minutes to 1.73 minutes, aligning with the set takt time, thereby enhancing operational efficiency and reducing time waste in the order picking and packing processes.